Dynamic modelling with kineto-static method and experiment validation of a novel controllable mechanical metal forming press. (5th January 2007) - He, Kai; Li, Weimin; Du, R.
This paper presents the design, dynamic modelling and experiment validation of a novel controllable mechanical metal forming press. The press is designed based on a hybrid 2-DOF planar mechanism. It is driven by a Constant Speed Motor (CSM) with flywheel and a servomotor simultaneously. The CSM provides the main power, while the servomotor tunes the velocity of the punch to realise different punch motions. Because of the loading variation of the metal forming process, the dynamics of the press is crucial for control and accuracy. In this paper, the dynamic model of the press is derived using the kineto-static method. The simulation shows that the servomotor mainly provides the power to overcome the inertia force for realising the desired punch trajectory. On the other hand, the CSM provides the main power for metal forming when the load is applied. The simulation results are tested in our custom-made 250 KN prototype. The experiments are conducted under three different loading conditions. The experimental results match well with the simulation results. This confirms the success of the design.